European works councils in practice: key research findings. Background paper (Dublin, 2009)
"European Works Councils (EWCs) are highly significant in terms of European industrial relations. They represent the first genuinely European institution of worker interest representation at enterprise level. They reflect the growing recognition of the need to respond to the ‘Europeanisation’ of business emerging from the Single European Market with the Europeanisation of worker representation, by supplementing existing national channels of information and consultation."